P19 Symptomatic Epstein Barr Virus (EBV) Hepatitis is uncommon, but occurs in patients of any age, including the elderly. (6th September 2011) - Vine, L; Shephard, K; Grimes, D; Bendall, R; Dalton, H
Abstract : Introduction: Epstein Barr Virus (EBV) infection typically presents as infectious mononucleosis (IM) in young adults with the classical triad of fever, sore throat and lymphadenopathy. Mildly abnormal liver function tests (LFTs) are common but symptomatic hepatitis is rare. Symptomatic, icteric, EBV hepatitis is rarely reported in those with IM and in the elderly. Aim: To review the demographics, presenting features and natural history with EBV hepatitis and to determine what factors might lead a clinician to consider a diagnosis of EBV hepatitis. Method: Retrospective study of 2100 patients attending the Jaundice Hotline, a fast track referral system for patients with jaundice at The Cornwall Royal Cornwall Hospital (1998–2011). EBV hepatitis was defined as: symptomatic hepatitis with positive serology for EBV (serology included EBV nuclear antigen, EBV viral capsid antigen (VCA) IgM and VCA IgG). All patients had no evidence of biliary obstruction or parenchymal liver disease on abdominal ultrasound examination (USS), and negative serology for other hepatotropic viruses (HAV, HBV, HCV, HEV, CMV). Other causes of parenchymal liver disease were also excluded by appropriate blood tests. Results: Of the total of 2100 consecutive patients with jaundice studied, 17 patients (10 males, 7 females) were diagnosed with EBV hepatitis. All patients were immunocompetent. 47% (8/17) of these patients were aged over 60 years (mean age 44 years, range 18–82). At presentation, mean (range) LFTs were: bilirubin 57 μmol/l (11–161), ALT 428 IU/l (34–1471), ALKP 339 IU/l (132–840). Only 3 patients presented as classical IM. 95% (16/17) had significant lymphocytosis and 82% (14/17) patients had splenomegaly on USS examination at initial assessment. Only 2 patients were unwell enough to be admitted to hospital. All patients fully recovered within 4–6 weeks. Conclusion: Symptomatic EBV hepatitis is uncommon and causes a self-limiting illness. EBV hepatitis is not usually associated with classical symptoms of IM and occurred in patients of a wide variety of ages. The diagnosis should be considered in patients of all ages presenting with hepatitis, including those with a cholestatic picture, and especially in those with a lymphocytosis and splenomegaly.